INOVASI DALAM KEBIJAKAN DAN REGULASI PERLINDUNGAN SAKSI DAN KORBAN DI INDONESIA - Suparman, Yusup; Elawati, Tuti (Gapenas Publisher, 2025)
This study examines innovations in policies and regulations regarding witness and victim protection in Indonesia, with a focus on strengthening the legal framework, institutional capacity, and implementation within the criminal justice system. The Witness and Victim Protection Agency (LPSK), as a non-ministerial government body, plays a strategic role in ensuring justice but continues to face challenges such as weak institutional structure, limited human resources, inadequate facilities and funding, and suboptimal use of information technology. This research employs a normative juridical approach complemented by limited empirical analysis of regulations, institutions, and policy implementation. The findings highlight the urgency of reforming witness and victim protection through revising Law No. 31 of 2014 using an omnibus law approach, formulating a grand design for witness and victim protection 2025–2045, establishing a dedicated trust fund, and developing restorative justice-based protection clinics. Furthermore, optimizing legal structures, enhancing regulatory quality, strengthening legal culture, and advancing digitalization through the national one-data system and electronic-based government system (SPBE) are key strategies. In conclusion, innovation in witness and victim protection policies and regulations in Indonesia must be directed toward institutional strengthening, improving civil service competence toward smart ASN, and ensuring sustainable funding to establish a modern, inclusive, and just national legal system.